Implementation of a psychomotor vigilance test to investigate the effects of driving fatigue on oil and gas truck drivers’ performance - Al-Mekhlafi, Al-Baraa Abdulrahman; Isha, Ahmad Shahrul Nizam; Al-Quraishi, Maged S.; Kanwal, Noreen (Frontiers in Public Health, 2023)
Introduction Driving fatigue has been shown to increase the risk of accidents and potentially fatal crashes. Fatigue is a serious risk that some drivers do not take seriously. Previous studies investigated the effects of driving fatigue in the Malaysian oil and gas transportation industry by employing survey questionnaires. However, they did not explain the behavior of fatigue. Besides, these results required validation by a more reliable method that can describe how fatigue occurs. Methods Thus, in this study, we used the Psychomotor Vigilance Test (PVT-192) and a short survey to address driving fatigue behavior and identify the influences of driving fatigue on driving performance in real life (on the road) with actual oil and gas tanker drivers. The total participants in the experimental study were 58 drivers. Results For the analysis, a Wilcoxon Signed Ranks Test, Z value and Spearman’s rho were used to measure the significant difference between the pre and post-tests of PVT and the correlation between the fatigue variables and driving performance. Discussion During the experiment’s first and second days, this study’s results indicated that driving fatigue gradually escalated. Likewise, there was a negative correlation based on the test of the relationship between the PVT data and the driving performance survey data. Additionally, the drivers suffer from accumulative fatigue, which requires more effort from the transportation company management to promote the drivers awareness of fatigue consequences.